Diagnosis of the environmental degradation of a segment of the River of the Peixe in Itabira (MG) and proposition of measures for its restoration (Research, Society and Development, 2019)
Anthropogenic activities near water courses cause negative environmental impacts in these, and may result in irreversible morphological, ecological and hydrological alterations. To restore the ecological balance of a water course, it is necessary to determine the level of degradation and river restoration potential, considering its physical, functional and environmental aspects. This research aimed at the elaboration of a diagnosis of the environmental and fluvial conditions of a section of Rio do Peixe, located in Itabira (MG), aiming at proposing intervention alternatives for the restoration of the environment. For that, field research, data analysis regarding water quality and observation were used. The section of Rio de Peixe analyzed, situated downstream of the homonymous dam, is 880 m in length. It should be highlighted that, due to the indicators related to habitat diversity, adjacent green areas and water quality, this section was subdivided into eight homogeneous sub-stretches. In general, the level of degradation was considered average, since despite the low degradation of the physical aspects, the absence of native vegetation resulted in a very high degradation regarding the environmental dimension. There was a potential for high restoration, thus, restoration techniques related to bioengineering were proposed, such as the application of biomass, cleaning, tree branches, suppression of exotic vegetation and planting of native seedlings. In addition to restoration, it is important that continuous monitoring be carried out and environmental education programs developed for the resident population near water courses.